An Analysis Upon Common Tribal Health Issues In Tribal Children In India: Understanding the Burden of Disease and Health Seeking Behavior in Tribal Children of India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
There is a heavy burden of communicable, no communicable and silentkiller genetic diseases prevalent in tribal communities. Many of the infectiousand parasitic diseases can be prevented with timely intervention, healthawareness, and information, education and communication (IEC) skilledactivities. In spite of the tremendous advancement in the field of preventiveand curative medicine, the health care delivery services in tribal communitiesare still poor and need amelioration and strengthening with sustenance on theguidelines suggested to achieve the targeted goals of health for all in India.Unless locality specific, tribe specific and need-based health care deliverysystem is evolved which is appropriate, acceptable, accessible, and affordable,the goal of health for all would remain a Utopian dream! The perception ofhealth and health seeking behaviour among the tribal children world over isintertwined with lots of factors – their traditional beliefs, practices, natureof interaction with physical environment and changing social, cultural andeconomic domain. Tribal population world over has been exposed to a rapidlychanging world around them, the depleted natural resources on which they aredependent and alien culture of monetary economy. Tribal children are mostly unable to cope with these new situations.Their social and cultural customs are in transition whereas in socio-economicfront they are lagging far behind from others. Globally, each yearmalnutrition is implicated in about 40% of the 11 million deaths of under-fivechildren in developing countries. Under nutrition is still the major problem inour country especially in underserved areas such as urban slums and ruralareas. So we undertook this study to assess the factors associated withmalnutrition and risk of infections among malnourished children.